Assignment 10 R10

#$&*

course Mth 158

2-22 4 pm

010. `* 10

Question: * 1.1.20 (was 1.1.12). Explain, step by step, how you solved the equation 5y + 6 = -18 - y

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

5y + 6 = -18 - y

To get the variable on one side of the equation, add y to both sides

6y + 6 = -18

Subtract 6 from both sides

6y = -24

Divide both sides by 6

Y= -4

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION WITH INSTRUCTOR COMMENT: 5y + 6 = 18 - y

Subtract 6 from both sides, giving us

5y = 12 - y

Add y to both sides,

5y + y = 12 or 6y = 12

divide both sides by 6

y = 2

INSTRUCTOR COMMENT: This is correct for equation 5y + 6 = 18 - y but the equation in the above note is 5y + 6 = -18 - y.

The solution to this equation is found by practically the same steps but you end up with y = -4.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

1.1.38 \ 44 (was 1.1.30). Explain, step by step, how you solved the equation (2x+1) / 3 + 16 = 3x

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First multiply each side by 3

2x + 1 + 48 = 9x

Add like terms

2x + 49 = 9x

Subtract 2x from each side

49 = 7x

Divide each side by 7

X = 7

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION:

(2x + 1) / 3 + 16 = 3x

First, multiply both sides of the equation by 3

2x +1 + 48 =9x or

2x + 49 = 9x

subtract 2x from both sides to get

49 = 7x

Divide both sides by 7 to get

x = 7.

STUDENT QUESTION

I was wondering at the end since it ended up 49 = 7x and you divide by 7 and say x = 7…would you have to

make it a -7 if you move it to the opposite side of the equation?

INSTRUCTOR RESPONSE

It's not a matter of 'moving things around', but a matter of adding or subtracting the same quantity on both sides, or multiplying or dividing both sides by the same quantity.

In this case both sides are divided by 7, which doesn't involve any negative signs.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* was 1.1.44 \ 36. Explain, step by step, how you solved the equation (x+2)(x-3) = (x+3)^2

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First use the distributive property

X^2 - 3x + 2x - 6 = x^2 + 3x + 3x + 9

Add like terms

X^2 - x - 6 = x^2 + 6x + 9

Subtract x^2 from both sides

-x -6 = 6x + 9

Add x to both sides

-6 = 7x + 9

Subtract 9 from both sides

-15 = 7x

Divide each side by 7

X= -15/7

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION: (x+2)(x+3) = (x+3)^2

First, we use the distributive property to remove the parenthesis and get

x^2 - x - 6 = x^2 + 6x + 9

subtract x^2 from both sides,

-x - 6 = 6x + 9

Subtract 9 from both sides

- x - 6 - 9 = 6x or -x - 15 = 6x

add x to both sides

-15 = 7x

Divide both sides by 7

x = -15/7

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* 1.1.52 (was 1.1.48). Explain, step by step, how you solved the equation x / (x^2-9) + 4 / (x+3) = 3 / (x^2-9).

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Multiply each side by (x^2 - 9)

X + 4(x-3) = 3

Use the distributive property

X + 4x - 12 = 3

Add like terms

5x - 12 = 3

Add 12 to both sides

5x = 15

Divide both sides by 5

X = 3

However, if you plug in x=3, u get a common denominator of 0, so in this case there is no solution

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

x / (x^2 -9) + 4 / (x+3) = 3 / (x^2 -9),

first factor x^2 - 9 to get

x / ( (x-3)(x+3) ) + 4 / (x+3) = 3 / ( (x-3)(x+3) ).

Multiply both sides by the common denominator ( (x-3)(x+3) ):

( (x-3)(x+3) ) * x / ( (x-3)(x+3) ) + ( (x-3)(x+3) ) * 4 / (x+3) = ( (x-3)(x+3) ) * 3 / ( (x-3)(x+3) ).

Simplify:

x + 4(x-3) = 3.

Apply the Distributive Law, rearrange and solve:

x + 4x - 12 = 3

5x = 15

x = 3.

If there is a solution to the original equation it is x = 3.

However x = 3 results in denominator 0 when substituted into the original equation, and division by 0 is undefined. So there is no solution to the equation.

STUDENT COMMENT

x / (x^2-9) + 4 / (x+3) = 3 / (x^2-9) Since you have like terms (x^2 - 9) on both sides, they cancel each other out

INSTRUCTOR RESPONSE

If something 'cancels' by multiplication or division, it has to 'cancel' from all terms. (x^2 - 9) is not a multiplicative or divisive factor of the term 4 / (x + 3) so that factor does not 'cancel'.

You can multiply or divide both sides by the same quantity, or add and subtract the same quantity from both sides.

Anything called 'cancellation' that doesn't result from these operations is invalid.

Because 'cancellation' errors are so common among students at this level, my solutions never mention anything called 'cancellation'.

If you multiply both sides of the equation

x / (x^2-9) + 4 / (x+3) = 3 / (x^2-9)

by (x^2 - 9), you get

( x / (x^2-9) + 4 / (x+3) ) * (x^2 - 9) = 3 / (x^2-9) * (x^2 - 9) so that

x / (x^2-9) * (x^2 - 9) + 4 / (x+3) * (x^2 - 9) = 3 / (x^2-9) * (x^2 - 9). The (x^2 - 9) does then 'cancel' from two of the three terms, but not from the third. You get

x + 4 / (x+3) * (x^2 - 9) = 3.

You're still stuck with an x^2 - 9 factor on one of the terms, and a denominator x - 3.

However this equation does represent progress. If you factor x^2 - 9 into (x-3)(x+3), things quickly simplify.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* 1.1.58 (was 1.1.54). Explain, step by step, how you solved the equation (8w + 5) / (10w - 7) = (4w - 3) / (5w + 7)

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First use the LCM (10w - 7)(5w + 7) to get rid of the fractions within the expression

40w^2 + 56w + 25w + 35 = 40w^2 - 28w - 30w + 21

Add like terms

40w^2 + 81w + 35 = 40w^2 - 58w + 21

Subtract 40w^2 from both sides

81w + 35 = -58w + 21

Add 58w to both sides

139w + 35 = 21

Subtract 35 from both sides

139w = -14

Divide each side by 139

W = -14/139

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * GOOD STUDENT SOLUTION:

1) clear the equation of fractions by multiplying both sides by the LCM (10w - 7)(5W + 7)

After cancellation the left side reads:

(5w+7)(8w + 5)

After cancellation the right side reads:

(10w - 7)(4w - 3)

multiply the factors on each side using the DISTRIBUTIVE LAW

Left side becomes: (40w^2) + 81w + 35

Right side becomes: (40w^2) - 58w + 21

3) subtract 40w^2 from both sides

add 58w to both sides

subtract 35 from both sides

Rewrite: 139w = - 14

Now divide both sides by 139 to get

w = - (14 / 139)

STUDENT QUESTION:

(5w+7)(8w+5) = (10w-7)(4w-3)

work what you can

40w^2 + 35 = 40w^2 +21

take away 40w^2 from both sides

didnt understand this one..;

INSTRUCTOR RESPONSE:

It doesn't look like you used the distributive law to multiply those binomials.

(5w+7)(8w+5) = 5w ( 8w + 5) + 7 ( 8w + 5)= 40 w^2 + 25 w + 56 w + 35 = 40 w^2 + 81 w + 35.

(10w-7)(4w-3) = 10 w ( 4 w - 3) - 7 ( 4 w - 3) = 40 w^2 - 30 w - 28 w + 21 = 40 w^2 - 58 w + 21.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question: * 1.1.70 (was 1.1.78). Explain, step by step, how you solved the equation 1 - a x = b, a <> 0.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First subtract 1 from both sides

-ax = b-1

Divide each side by -a

X = (b-1)/-a

Now multiply the right half of the equation by -1/-1 to get rid of the negative denominator

X= (1-b)/a

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Start with

1 -ax = b, a <> 0.

Adding -1 to both sides we get

1 - ax - 1 = b - 1,

which we simplify to get

-ax = b - 1.

Divide both sides by -a, which gives you

x = (b - 1) / (-a). Multiply the right-hand side by -1 / -1 to get

x = (-b + 1) / a or

x = (1 - b) / a. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* extra problem (was 1.1.72). Explain, step by step, how you solved the equation x^3 + 6 x^2 - 7 x = 0 using factoring.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Factor x out of the left side of the equation

X( x^2 + 6x - 7) = 0

Now factor

X (x+7)(x-1) = 0

Since the left side of the equation equals 0,

X= 0, 1, -7

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

x^3 + 6 x^2 - 7 x = 0 factor x out of the left-hand side:

x(x^2 + 6x - 7) = 0. Factor the trinomial:

x ( x+7) ( x - 1) = 0. Then

x = 0 or x + 7 = 0 or x - 1 = 0 so

x = 0 or x = -7 or x = 1. **

STUDENT QUESTION

I don’t understand this part of the equation x = 0 or x + 7 = 0 or x - 1 = 0 so

x = 0 or x = -7 or x = 1 ??? where do you get all of this from???

INSTRUCTOR RESPONSE

x ( x+7) ( x - 1) = 0

says that three different quantities, multiplied together, give you zero.

Now if three quantities multiplied together give you zero, what is the one thing you know for sure?

You know for sure that one of them is zero, because if you multiply three quantities that aren't zero you don't get zero (more specifically if you multiply three numbers, none of which are zero, you don't get zero).

The three quantities are x, x + 7 and x - 1. The only way you can get zero by multiplying these quantities is if one of them is zero.

So if

x ( x+7) ( x - 1) = 0

you know that x = 0, or x + 7 = 0, or x - 1 = 0.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* 1.1.90 (was 1.2.18). The final exam counts as two tests. You have scores of 86, 80, 84, 90. What score do you need on the final in order to end up with a B average, which requires an average score of 80, and an A average, which requires a score of 90?

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

Find the average of the given amounts first- 85

Next, we need an equation to figure out the value of the needed score

(85 + 2x)/3 works

85 is the average of course, x, is the needed score- it’s multiplied by 2 because the test is counted twice.

We then divide that expression by 3 since we have three scores- 85, x, x

Since 80 is the desired score of the final average, the full equation should read

(85 + 2x)/3 = 80

Now solve for x

Multiply each side by 3

85 + 2x = 240

Subtract 85 from each side

2x = 155

Divide each side by 2

X=77.5

For the second equation, the desired final average is 90, so the expression now reads

(85 + 2x)/3 = 90

Multiply each side by 3

85 + 2x = 270

Subtract 85 from each side

2x= 185

Divide each side by 2

X= 92.5

confidence rating #$&*:3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * This can be solved by trial and error but the only acceptable method for this course, in which we are learning to solve problems by means of equations, is by an equation.

Let x be the score you make on the exam.

The average of the four tests is easy to find:

4-test average = ( 86 + 80 + 84 + 90 ) / 4 = 340 / 4 = 85.

The final grade can be thought of as being made up of 3 parts, 1 part being the test average and 2 parts being the exam grade. We would therefore have

final average = (1 * test average + 2 * exam grade) / 3.

This gives us the equation

final ave = (85 + 2 * x) / 3.

If the ave score is to be 80 then we solve

(85 + 2 * x) / 3 = 80.

Multiplying both sides by 3 we get

85 + 2x = 240.

Subtracting 85 from both sides we have

2 x = 240 - 85 = 155

so that

x = 155 / 2 = 77.5.

We can solve

(340 + x) / 5 = 90

in a similar manner. We obtain x = 92.5.

Alternative solution:

If we add 1/3 of the test average to 2/3 of the final exam grade we get the final average. So (using the fact that the test ave is 85%, as calculated above) our equation would be

1/3 * 85 + 2/3 * x = final ave.

For final ave = 80 we get

1/3 * 85 + 2/3 * x = 80.

Multiplying both sides by 3 we have

85 + 2 * x = 240.

The rest of the solution goes as before and we end up with

x = 77.5.

Solving 1/3 * 85 + 2/3 * x = 90 we get x = 92.5, as before. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* 1.1.82 (was 1.1.90). Explain, step by step, how you solved the equation v = -g t + v0 for t.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

V = -gt + v0

Solve for t

Subtract v0 from both sides

V - v0 = -gt

Divide each side by -g

(v - v0)/-g = t

Or

(-v + v0)/g = t

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * NOTE: v0 stands for v with subscript 0; the whole expression v0 stands for the name of a variable. It doesn't mean v * 0.

Starting with v = -g t + v0, add -v0 to both sides to get

v - v0 = -gt.

Divide both sides by -g to get

(v - v0) / (-g) = t

so that

t = -(v - v0) / g = (-v + v0) / g.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

*********************************************

Question:

* 1.1.82 (was 1.1.90). Explain, step by step, how you solved the equation v = -g t + v0 for t.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

V = -gt + v0

Solve for t

Subtract v0 from both sides

V - v0 = -gt

Divide each side by -g

(v - v0)/-g = t

Or

(-v + v0)/g = t

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * NOTE: v0 stands for v with subscript 0; the whole expression v0 stands for the name of a variable. It doesn't mean v * 0.

Starting with v = -g t + v0, add -v0 to both sides to get

v - v0 = -gt.

Divide both sides by -g to get

(v - v0) / (-g) = t

so that

t = -(v - v0) / g = (-v + v0) / g.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):ok

------------------------------------------------

Self-critique Rating:3

#*&!

&#Very good responses. Let me know if you have questions. &#